2021
DOI: 10.5334/dsj-2021-011
|View full text |Cite
|
Sign up to set email alerts
|

Sample Identifiers and Metadata to Support Data Management and Reuse in Multidisciplinary Ecosystem Sciences

Abstract: Physical samples are foundational entities for research across biological, Earth, and environmental sciences. Data generated from sample-based analyses are not only the basis of individual studies, but can also be integrated with other data to answer new and broader-scale questions. Ecosystem studies increasingly rely on multidisciplinary team-science to study climate and environmental changes. While there are widely adopted conventions within certain domains to describe sample data, these have gaps when appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…We used the practices identified in our systematic review to create our ESS‐DIVE Community Space on GitHub (https://github.com/ess%2Ddive%2Dcommunity), where six teams of scientists are developing and managing data and metadata reporting formats (e.g., Bond‐Lamberty et al., 2021; Damerow et al., 2021; Ely et al., 2021). We note that initial drafts of documentation were created and reviewed using other collaborative cloud‐based tools (e.g., Google Sheets), then migrated to GitHub for community feedback.…”
Section: Resultsmentioning
confidence: 99%
“…We used the practices identified in our systematic review to create our ESS‐DIVE Community Space on GitHub (https://github.com/ess%2Ddive%2Dcommunity), where six teams of scientists are developing and managing data and metadata reporting formats (e.g., Bond‐Lamberty et al., 2021; Damerow et al., 2021; Ely et al., 2021). We note that initial drafts of documentation were created and reviewed using other collaborative cloud‐based tools (e.g., Google Sheets), then migrated to GitHub for community feedback.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the extended scope may be accommodated in community-specific extensions, while other user communities might need entirely different sample description schemas. Other use cases need to integrate with existing schemas and vocabularies through crosswalks (Damerow et al, 2021). Figure 3 illustrates the concept of community extensions to core description schemas ('bullseye') and the parallel existence of multiple description schemas.…”
Section: Describing Samples For Discovery and Reusementioning
confidence: 99%
“…But there are also differences in the choice of schemes for PIDs and the core elements. Upon reviewing nine different PID schemes, Damerow et al (2021) concluded that IGSN (International GeoSample Number) is the most suitable scheme for physical samples, including but not limited to geosamples. ISamples' position is to treat all PIDs used equally as first‐class citizens (e.g.…”
Section: Recent Developmentmentioning
confidence: 99%
“…These issues are long recognized by the data infrastructure community and multiple projects are actively working to make sample data FAIR (Findable, Accessible, Interoperable, and Reusable). These projects include the Internet of Samples (iSamples, Davies et al, 2021), Digital Specimens (DS, DiSSCoTech, 2020), BCoN's Extended Specimens (Lendemer et al, 2020), and US DOE's work (Damerow et al 2021). In this poster, we report the recent development of iSamples in the context of these other projects.…”
Section: Introductionmentioning
confidence: 99%